2010
DOI: 10.1038/cr.2010.183
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB and STAT3 – key players in liver inflammation and cancer

Abstract: Hepatocellular carcinoma (HCC), the major form of primary liver cancer, is one of the most deadly human cancers. The pathogenesis of HCC is frequently linked with continuous hepatocyte death, inflammatory cell infiltration and compensatory liver regeneration. Understanding the molecular signaling pathways driving or mediating these processes during liver tumorigenesis is important for the identification of novel therapeutic targets for this dreadful disease. The classical IKKβ-dependent NF-κB signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
833
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,002 publications
(863 citation statements)
references
References 96 publications
23
833
1
6
Order By: Relevance
“…While safety remains a point of concern, given the fact that STAT3-null mice are embryonically lethal, tissue-specific STAT3 deletion experiments have indicated that STAT3 may not be essential for the survival of normal differentiated cells. These results provide further evidence that it may be safe to target STAT3 for HCC therapy [206].…”
Section: Role Of Stat3 In Oncogenic Transformationmentioning
confidence: 56%
“…While safety remains a point of concern, given the fact that STAT3-null mice are embryonically lethal, tissue-specific STAT3 deletion experiments have indicated that STAT3 may not be essential for the survival of normal differentiated cells. These results provide further evidence that it may be safe to target STAT3 for HCC therapy [206].…”
Section: Role Of Stat3 In Oncogenic Transformationmentioning
confidence: 56%
“…Both proteins are not only persistently activated in cancer and essential for transducing cytoplasmic signals from extracellular stimuli, but they also function as nuclear transcription factors required for regulating genes involved in tumor proliferation, survival, angiogenesis and invasion, in addition to genes encoding key cancerpromoting inflammatory mediators (Karin and Greten, 2005;Baud and Karin, 2009;Yu and Jove, 2004;Yu et al, 2007;Darnell, 2002). NF-κB and STAT3 play a critical role in many cancers including, hepatic (He and Karin, 2011), prostate (Shanmugam et al, 2011), Lung (Tyagi et al, 2009) and breast cancer (Seo et al, 2012) which was evident from the previous reports.…”
Section: Nuclear Factor -κBmentioning
confidence: 76%
“…In tumors, STAT3 directly interacts with the NF-κB family member RelA, trapping it in the nucleus and thereby contributing to constitutive NF-κB activation in tumor (Lee et al, 2009). Ultimately, STAT3 and NF-κB also co-regulate numerous oncogenic and inflammatory genes (Darnell et al, 2002;Yu and Jove, 2004;Yu et al, 2007;Ogura et al, 2008;He and Karin, 2011). Continuous deregulation of these genes in tumor cells and the tumor microenvironment by persistently activated STAT3 and NF-κB-in contrast to their tightly controlled regulation in normal physiology is crucial for inflammation and malignant progression.…”
Section: Nuclear Factor -κBmentioning
confidence: 99%
“…Third, many cytokines like IL-6 induced by NF-κB or STAT3 can feedback to induce STAT3 and NF-κB activation (Gao et al, 2007;Sansone et al, 2007;Grivennikov and Karin, 2008). Through their functional interaction, NF-κB and STAT3 collaboratively promote tumor development via induction of pro-tumorigenic genes including genes in angiogenesis and hypoxia, chemokines and immunosuppressive cytokines (Bollrath and Greten, 2009;Atkinson et al, 2010;He and Karin, 2011).…”
Section: Stats Signaling Transduction Pathwaymentioning
confidence: 99%